Assessing employee engagement and employee performance in Indonesian state-owned enterprises during Covid-19 pandemic - Adhietya Saputra; Armendra Armendra; Iman Permana (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
The COVID-19 Pandemic has changed the way companies operate due to the implementation of working-from-home or remote-working policies. This shift in working conditions affects employees' psychological well-being and the level of uncertainty they experience, which can have an impact on their engagement and performance. A literature review reveals recent research that proposed the '5C model' (conciliation, cultivation, confidence, compensation, and communication) to improve employee engagement. However, no further research was found that demonstrates the validation of the 5C model by using a quantitative methodology approach. This study aims to investigate the main factors of employee engagement that can lead to employee performance during the COVID-19 Pandemic by using a quantitative technique to validate the 5C model. Research data were collected from 360 respondents who worked in State-owned Enterprises (SOEs), including SOEs' subsidiaries and affiliates. SMART PLS 3.3 was used to examine the research model based on the data received from the surveys. The result of this study reveals that conciliation, cultivation, confidence, and communication are the dimensions of employee engagement. The study also demonstrates that employee engagement is the direct antecedent of employee performance. The contribution of this research is two-fold. First, it demonstrates a quantitative technique to validate the 5C model for improving employee engagement. Second, from a managerial standpoint, it proposes action plans that can be taken to increase employee engagement and performance.